BUSINESS MODEL ANALYSIS OF A CULINARY MICROENTERPRISE USING THE BUSINESS MODEL CANVAS FRAMEWORK - Diana Sari; M.Oktavianur (PT. Jurnal Center Indonesia Publisher, 2026)
This study analyzes the business model of a culinary microenterprise in Indonesia using the Business Model Canvas (BMC) framework proposed by Osterwalder and Pigneur (2010). A qualitative descriptive method was employed, utilizing in-depth interviews, observations, and documentation. The findings reveal that although the enterprise has not formally implemented a structured business model, all nine elements of the BMC are naturally reflected in its operational practices. The customer segments consist of students, workers, and the wider community seeking affordable and fast-serving meals. The value propositions emphasize affordability, consistent flavors, and friendly customer service. Key resources include human resources, equipment, raw materials, and financial capital, while key partnerships involve employees, suppliers, and customers. Revenue streams arise from food and beverage sales and delivery services, supported by direct sales channels and simple promotional strategies. This study aligns with the literature highlighting the importance of BMC in strengthening MSME competitiveness (Alifiyah & Budiman, 2021; Dwisanto & Ifghaniyafi, 2024). The findings contribute to MSME development research by demonstrating the relevance of the BMC as a strategic tool for enhancing sustainability in small-scale culinary businesses.